The Influence of Collaborative Learning Model on Scientific Argumentation Skills and Student Learning Outcomes in Social Studies Subjects for Grade V - Feby Ramadhani; Rosleny Babo; Hidayah Quraisy (LPPM Universitas PGRI Sumatera Barat, 2023)
The purpose of this research is directed to know and understand the significance of the application of collaborative learning models to scientific argumentation skills and student learning outcomes. The research method used is a quantitative method. The type of research used is a Quasi Experimental Design with the research design used is a Nonequivalent Control Group Design which is almost the same as the pretest-posttest Control Group design. This research was conducted at MIN 3 Jeneponto which is located at Pinjongga Beroanging Village, Bangkala Barat District, Jeneponto Regency. The population of this study were all students of MIN 3 Jeneponto which consisted of 3 upper classes of 6 groups with a total of 124 upper class students. The sampling technique used was purposive sampling, so that a sample of 36 people was obtained with details of 18 VA students and 18 class 5 B students, class 5 was chosen as the sample in this study because they could be invited to work together, class 5 a as the experimental class and class 5 b as the control class. The data collection technique is a method used by researchers to obtain data. Data collection techniques used in this study are Observation, Tests, and Documentation. Based on the results of the study, there was an influence of scientific argumentation skills using the Collaborative learning model on fifth grade students at MIN 3 Jeneponto. This can be seen from the high categorization obtained by students in the experimental class.